GERAKAN JULID FI SABILILLAH: RESPONS TERHADAP KONFLIK ISRAEL-PALESTINA TINJAUAN ETIKA KOMUNIKASI DALAM TAFSIR - Abdillah, Muhammad Torieq; Ansari, Panji (UIN ANTASARI BANJARMASIN, 2024)
The never-ending conflict between Israel-Palestine has resulted in a massive response on social media, particularly receiving special attention from the Indonesian people through the julid fi sabilillah movement led by Erlangga Greschinov. This research aims to determine existing communication ethics according to the interpretation of the emergence of the julid fi sabilillah movement as a response to the Israel-Palestine conflict. This research is a qualitative-descriptive research using the book Julid fi Sabilillah Gerakan Netizen di Jagat Maya Melawan Penjajahan Zionis Israel atas Palestina; Etika Berkeluarga, Bermasyarakat, dan Berpolitik (Tafsir Al-Qur’an Tematik) and Tafsir Ibnu Katsir as a secondary source and tweets snippets on X. The results of this research show that the julid fi sabilillah movement did several things, such as not doing it to just anyone, doing doxing as well as mentally condemning the IDF, providing positive narratives, and reporting the results they achieved. Apart from that, if it is related to the interpretation of communication ethics, what the julid fi sabilillah movement did is not something to worry about considering that they implemented honesty, accuracy of information, constructive criticism, responsibility and fairness.